1994
DOI: 10.1007/bf02361249
|View full text |Cite
|
Sign up to set email alerts
|

A case of metastatic chondrosarcoma of the stomach

Abstract: A case of metastatic chondrosarcoma of the stomach in a 34-year-old female is reported. This patient had been diagnosed as having chondrosarcoma of the right knee and was operated on in 1984. Thereafter, there was repeated local recurrence and operations were performed on multiple metastases, including those of the lung, brain, ovary and spleen. In September, 1990, the patient was readmitted because of advanced anemia. Gastroendoscopy disclosed a firm elevated lesion with central irregular erosion. Histologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
1
11
0
1
Order By: Relevance
“…25,26 Synchronous metastases to other organs such as the heart, 27 thyroid, 28 stomach, or pancreas are often reported at the time of diagnosis of lung metastases. [29][30][31] An aggressive surgical approach to isolated metastases is recommended, 25,[32][33][34] and the reported cases with sarcoma metastases to the pancreas were treated according to these recommendations. 29,35 Detectable widespread metastatic disease developed soon after pancreatectomy in our patient with a chondrosarcoma, who underwent excision of mediastinal metastases 2 years before the detection of a pancreatic metastasis.…”
Section: Methodsmentioning
confidence: 99%
“…25,26 Synchronous metastases to other organs such as the heart, 27 thyroid, 28 stomach, or pancreas are often reported at the time of diagnosis of lung metastases. [29][30][31] An aggressive surgical approach to isolated metastases is recommended, 25,[32][33][34] and the reported cases with sarcoma metastases to the pancreas were treated according to these recommendations. 29,35 Detectable widespread metastatic disease developed soon after pancreatectomy in our patient with a chondrosarcoma, who underwent excision of mediastinal metastases 2 years before the detection of a pancreatic metastasis.…”
Section: Methodsmentioning
confidence: 99%
“…For the remaining malignancies of the bone or soft tissue, only case studies were obtained. Ovarian metastases were described in patients with (haem)angiosarcoma (Hermann et al, 1984;Young and Scully, 1990), chondrosarcoma (Young and Scully, 1990;Konishi et al, 1994), desmoplastic small round cell tumour (Young et al, 1992a, b;Zaloudek et al, 1995;Elhajj et al, 2002;Parker et al, 2002;Fang et al, 2008;Ota et al, 2010), clear cell sarcoma (Nugent et al, 2009) and other tumours (Winfield et al, 2007).…”
Section: Bone and Soft Tissue Tumoursmentioning
confidence: 99%
“…Ozaki et al reported that the histological grade is correlated with the metastasis rate whereas size and location has no influence on the occurrence of metastasis [5]. The stomach is an uncommon site for metastatic involvement in chondrosarcoma, the first case was reported in 1994 by Konishi et al [6]. The most common primaries are melanoma, tumors of breast and lung.…”
Section: Discussionmentioning
confidence: 99%